PUI: Organisasi dan Perkembangannya Sejak Berdiri Hingga Pemilu 2009 - Emil Permanasari (STAI AL-FALAH CICALENGKA, 2019)
Islamic Community Unity develops in the form of conflict or disintegration, such as: how they choose to leave the members of the Masyumi major party or postpone the implementation of the 4th and 5th Islamic Society Unity Congress (PUI) efforts to explain what is needed. The development of Islamic Unity until the reform era was still in a